(untitled) (Research, Society and Development, 2021)
The production of insects as a source of nutrients represents a sustainable, attractive, and adequate production alternative to satisfy the growing demand for food, especially for animal nutrition. This is a nutritional strategy that can be considered mainly by the food industry since, compared to other commonly used foods such as animal flour and soybean meal, it can provide significant amounts of proteins, lipids, minerals, among other nutrients. These insects can be fed with agricultural residues and organic waste; being this one of the most important advantages that reinforces the use of this ingredient to feed animals. This strategy also reduces production costs and intervenes in the development of beneficial microbiota. Moreover, it reduces competition for food resources and insects act as immunomodulators. Currently, some studies highlight the use of various insect meals with the total inclusion or substitution of conventional sources of protein; an ingredient that offers significant results of zootechnical interest, generating a positive impact on the productive system, for which it deserves to be highlighted. The objective of this literature review is to highlight the use of insects in animal nutrition; mainly in aviculture as an economically viable alternative for the producer in terms of cost reduction, without affecting the productive performance of animals. In this sense, highlighting this issue as a new perspective in the animal feed industry and the livestock sector is of big importance.